Development of Dutatani Website Using Rapid Application Development - Rosa Delima; Halim Budi Santosa; Joko Purwadi (IJITEE (International Journal of Information Technology and Electrical Engineering), 2017)
Rapid Application Development (RAD) is a methodology used to develop software. This method is able to reduce time to develop software. This becomes consideration in order to choose the Rapid Application Development as a methodology to develop Dutatani Website. Dutatani is a portal and a part of Integrated Agriculture Information System (IAIS). IAIS is an agriculture information system that has some subsystems that are connected and linked to each other. It also has an integrated database. In particular, Dutatani is able to manage user, manage content, and manage link in the IAIS. This website will be a link to other applications in the IAIS. This article especially discusses the development of the Dutatani Website using Rapid Application Development that is implemented by combining iterative development and system prototyping. There are some phases in the development using the RAD: planning, analysis, main design specific design, implementation and testing, and integrating prototype. This system was developed by a team which consists five members. The implementation of this prototyping technique was done by dividing five people into two groups in which each group had different responsibilities to different module/functions. This website had been developed within 150 days. Thus, in implementing the RAD, it is important for the team leader to monitor continuously. Monitoring is a useful technique to ensure the productivity and performance of each members in order to gain optimal development process.